Modernism and the ordinary - Olson, Liesl (Oxford University Press, 2009)
This study overturns conventional accounts of the modernist period as primarily drawn toward the new, the transcendent, and the extraordinary. Liesl Olson shows how modernist writers were preoccupied, instead, with the unselfconscious actions of everyday life, even in times of political crisis and war.